Efecto de la tecnología agcelence en el desarrollo y producción del hibrido de maíz iniap`h-601´, en la zona de Quinsaloma, provincia de Los Ríos - Arizala Pino., Rubén Darío (2015)
The research proposal was made at the farm of Mr. Secundino Isidro Arízala Aguirre, located in the Quinsaloma Canton Campus Estero de Piedra, industry The Guabito, whose coordinates are UTM 694725, 9865000 georeferenced with PSA DATUM 56. The average temperature is 25, 4 C, annual rainfall of 1,398 mm and 869.4 hours heliophany of year, also has a rainfall of 1,096 mm and a wind speed of 2 km / h. The soil is regular topography with altitude of 30 meters, has clay loam texture and good drainage. The genetic material that was used was the hybrid maize hybrid lNlAP "H-601", which consist of a combination of seeding the crop and doses of the fungicide Opera, Tilt and Amistar, in doses of 500 cc treatments were evaluated / was compared to a control without application. The design was Randomized Complete Blocks factorial arrangement A x B, with proof of Tukey multiple range at 95% confidence. During the course of the investigation the following agronomic practices such as soil testing, soil preparation, planting, weed control, plant protection, irrigation, fertilization and harvesting were performed.......